Jean-Clet Martin, Logique de la science-fiction : de Hegel à Philip K. Dick (2017) - Jean-Loup Héraud (ReS Futurae)
In his book Logique de la science-fiction : de Hegel à Philip K. Dick, Jean-Clet Martin gives to read some emblematic authors of contemporary science fiction (so as Asimov, Van Vogt, p. Anderson, P. K. Dick..) in light of the major categories of being that Hegel declines in his Science of Logic (1812). Through this confrontation, the aim of the author is to confer new forms of intelligibility to this literary genre, and in an other way to reactualise the hegelian ontological project to write a logic of the world. If science-fiction explores the literary creation of imaginary worlds contradicting the familiar logic of our world, the hegelian logic explores the steps of the deep reality of « Being », « Essence » and finally the « Concept ». The endless travels of space conquest opening The Cycle of Foundations (Asimov) becomes the metaphor of travel in the spirit through the dialectical moments of Being : this adventure recap a knowledge that exceedsthe limits of our own world. Against the restrictive ontology of our world, an expansive and explosive ontology is in the real background of the whole of science-fiction